Endovascular Treatment for Basilar Artery Occlusion: Revisiting Evidence From Randomized Clinical Trials - Sherief Ghozy; Amr Ehab El‐Qushayri; Mohamed Elfil; Alis J. Dicpinigaitis; Krishna Amuluru; Mohammad El‐Ghanem; Chirag D. Gandhi; Fawaz Al‐Mufti (Stroke: Vascular and Interventional Neurology, 2025)
Background Acute ischemic stroke attributed to basilar artery occlusion is known to be associated with high rates of mortality and disability. However, the previous clinical trials did not provide evidence to support the efficacy of endovascular treatment (EVT) in patients with basilar artery occlusion. The purpose of this study was to provide updated evidence about EVT's benefits and safety profile with the recent update from both the Endovascular Treatment for Acute Basilar Artery Occlusion (ATTENTION) and the Basilar Artery Occlusion Chinese Endovascular Trial (BAOCHE) trials. Methods We searched for eligible articles from inception to November 1, 2022, in 5 databases and included all randomized controlled trials with no restrictions on the publication date or language. Meta‐analysis statistics were performed using R software version 4.2.1. Results The rate of modified Rankin scale score of 0 to 3 was significantly higher in the EVT group compared with best medical treatment (risk ratio [RR], 1.54 [95% CI, 1.16–2.04]; P value = 0.002), and the same was observed for the rate of modified Rankin scale score 0 to 2 (RR, 1.83 [95% CI, 1.08–3.08]; P value = 0.024). Moreover, there was a significant reduction in the 90‐day mortality in the EVT group (RR, 0.76 [95% CI, 0.65–0.89]; P value = 0.002). However, there was a significantly higher rate of symptomatic intracerebral hemorrhage in the EVT group compared with best medical treatment (RR, 7.48 [95% CI, 2.27–24.61]; P value <0.001). Conclusions EVT may confer a clinical benefit to patients with acute ischemic stroke caused by basilar artery occlusion. Because of the small number of included studies and because all of them were conducted in the Chinese population, further trials might be needed to confirm and further investigate the generalizability of these results.